Review of Subcontractor Selection Criteria in Construction Services Using Analytic Network Process (ANP) - Benefit Cost Risk (BCR) - Susetyo Rohadi; Widi Hartono; Dewi Handayani; Andi Dwi Putranto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
To develop effective techniques for selecting subcontractors, this research set out to determine which factors should take precedence and which alternatives may be useful in terms of BCR, benefits, costs, and risks. Based on the results Project managers, control managers, procurement bureau managers, production managers, finance bureau managers, and employees/staff directly related to procurement activities (i.e., procurement staff) were randomly selected to participate in in-depth interviews and questionnaires to gather data for the study of subcontractor selection criteria in construction services. Analytical Network Process (ANP) using BCR network structure methodology is used to analyze the data in this study. Benefit, Cost, and Risk (BCR) study of the subcontractor selection process yielded the following results: control criteria. As a result, the decision-making process for choosing subcontractors shifts its focus to other technical competency factors, which might provide advantages.